Fun with english: An english learning assistance at SMK Warga Surakarta - Hidayati, Diyah Nur; Yafi, Mohammad Ali; Santoso, Aan Budi; Ambarsari, Rika Yuni; Sasmito, Luncana Faridhoh; Asfuri, Ninda Beny (Nur Science Institute, 2022)
Mastery of English languages is vital in preparing graduates to compete on a global scale in order to improve the quality of human resources in the world of education. As a result, efforts to improve English mastery for the academic community are evidence of an institution's seriousness in realizing its commitment to international standard institutions. The Covid-19 pandemic is currently affecting a variety of industries, particularly education. The Study from Home (SFH) system has now been adopted by many educational institutions. This, however, isn't enough. Many parents express their dissatisfaction with having to accompany their children to their home study sessions. This is not a major issue for students from upper middle-class families, as their parents will almost certainly provide facilities and private tutoring. Students from lower-middle-class families have a different situation. They must learn to be self-sufficient within the confines of their current circumstances. One of the private vocational schools in Central Java is SMK Warga Surakarta. Students in this school have difficulty understanding English sentences, according to the results of interviews with English teachers. As a result, English language training is required at SMA Warga in Surakarta to improve students' comprehension.